DETERMINATION OF VITAMIN CONTENT IN MULBERRY (MORUS ALBA) LEAF EXTRACT - Ibrohim Rahmonovich Askarov; Tillavoldiyeva Mohichehra Akromjon qizi; Azizbek Sobirovich Khojikulov (Scholars Digest Publishing, 2025)
The present study investigates the chemical composition of Morus alba (white mulberry) leaves, focusing on the concentration of water-soluble vitamins extracted from dried leaf samples. Given the increasing interest in plant-based bioactive compounds, mulberry leaves are recognized for their potential health-promoting properties, including antioxidant, anti-inflammatory, and metabolic regulatory effects. Using High-Performance Liquid Chromatography (HPLC), the quantitative analysis revealed the presence of key B-group vitamins (B1, B2, and B3) and vitamin C. The results indicate a progressive increase in vitamin concentration in the order of B1 < B2 < B3, highlighting the rich nutritional profile of the extract. This finding underscores the potential of mulberry leaf extract as a natural source of essential micronutrients and supports its application in nutraceutical and functional food industries. Additionally, the study discusses the relevance of glycosides, alkaloids, and organic acids identified in the extract, as well as their synergistic role in promoting human health.
Keywords: Mulberry leaf, vitamin C, vitamin B1, vitamin B2, vitamin B3, glycoside, acid, compounds, arctium, alkaloids, extract, minerals, HPLC.